Depigmenting potential of lichen extracts evaluated by in vitro and in vivo tests - Paola Malaspina; Erica Catellani; Bruno Burlando; Daniele Brignole; Laura Cornara; Miriam Bazzicalupo; Simona Candiani; Valentina Obino; Vincenzo De Feo; Lucia Caputo; Paolo Giordani (PeerJ, 2020)
Melanin is the main pigment of human skin, playing the primary role of protection from ultraviolet radiation. Alteration of the melanin production may lead to hyperpigmentation diseases, with both aesthetic and health consequences. Thus, suppressors of melanogenesis are considered useful tools for medical and cosmetic treatments. A great interest is focused on natural sources, aimed at finding safe and quantitatively available depigmenting substances. Lichens are thought to be possible sources of this kind of compounds, as the occurrence of many phenolic molecules suggests possible effects on phenolase enzymes involved in melanin synthesis, like tyrosinase. In this work, we used four lichen species, Cetraria islandica Ach., Flavoparmelia caperata Hale, Letharia vulpina (L.) Hue, and Parmotrema perlatum (Hudson) M. Choisy, to obtain extracts in solvents of increasing polarity, viz. chloroform, chloroform-methanol, methanol, and water. Cell-free, tyrosinase inhibition experiments showed highest inhibition for L. vulpina methanol extract, followed by C. islandica chloroform-methanol one. Comparable results for depigmenting activities were observed by means of in vitro and in vivo systems, such as MeWo melanoma cells and zebrafish larvae. Our study provides first evidence of depigmenting effects of lichen extracts, from tyrosinase inhibition to cell and in vivo models, suggesting that L. vulpina and C. islandica extracts deserve to be further studied for developing skin-whitening products.